Not Up for Discussion: Applying Lukes' Power Model to the Study of Health System Corruption; Comment on "We Need to Talk About Corruption in Health Systems" - Lucy Reynolds (Kerman University of Medical Sciences, 2019)
This companion paper suggests the potential benefits of applying Steven Lukes' dimensions of power model to the study of corruption in health systems. Lukes' model sets out three "faces of power" classified by their influence on political discourse, resulting in overt, covert and latent discussion of issues depending on the degree of their alignment with the agenda of dominant power interests. His concept that differential access to public discourse varies according to this alignment implies the potential for identifying more serious forms of corruption by the mismatch between their practical importance and the amount of open debate addressing them. These two variables are in practice inversely related, and do not, as might be expected, correlate, with more important topics receiving more public attention. Lukes' model would predict and can explain such inversion of public priorities, which tells us that observed suppression of public debate might efficiently direct the interest of researchers and the efforts of those seeking to further the public good on to the key issues needing discussion and resolution. The commentary goes on to examine whether the most serious and dangerous forms of corruption might therefore also be the most invisible, and suggests that whistleblower reports should be considered a key data source for research into high-level corruption in health systems, including redirection of policy decisions away from those which are in the public interest.